CORRECTION OF DEFORMITY OF THE BACK AND END OF THE NOSE USING THE “OPEN” METHOD (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
One of the most complex and important sections of facial reconstructive surgery is the implementation of reconstructive and corrective operations aimed at eliminating nasal deformities. Along with the increase in the number of patients with congenital and post-traumatic deformities of the nose, defects after treatment of oncological diseases, in recent years the number of patients with the consequences of unsuccessful aesthetic surgeries has increased significantly.